Antibacterial and Cytotoxic Activities of Pinus tropicalis and Pinus elliottii Resins and of the Diterpene Dehydroabietic Acid Against Bacteria That Cause Dental Caries - Silva, Kelly Regina da; Damasceno, Jaqueline Lopes; Inácio, Moana de Oliveira; Abrão, Fariza; Ferreira, Natália Helen; Tavares, Denise Crispim; Ambrosio, Sergio Ricardo; Veneziani, Rodrigo Cassio Sola; Martins, Carlos Henrique Gomes (Frontiers in Microbiology, 2019)
Considering the impact of dental caries on public health and the wide biological potential described for species belonging to the genus Pinus, here we investigate the antibacterial activity of the P. elliottii and P. tropicalis resins and of the diterpene dehydroabietic acid (DHA) against cariogenic bacteria. For this purpose, we have determined the minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC) of the resins and of the diterpene. We have also investigated the biofilm inhibition ability (through MBIC50 determination), as well as the synergistic effect (through fractional inhibitory concentration index) and the cytotoxic potential (through XTT assay) of the P. elliottii and P. tropicalis resins. The resins gave promising MIC and MBC values, which ranged from 12.5 to 400 μg/mL; DHA provided MIC and MBC values ranging from 25 to 400 μg/mL. The MICB50 values ranged from 0.78 to 400 μg/mL for the resins. Neither additive nor synergistic effects emerged for the combinations of one of the resins with chlorhexidine. The cytotoxic activity was ≥ 312.5 μg/mL and ≥ 156.3 μg/mL for the P. elliottii and P. tropicalis resins, respectively. The resins showed antibacterial activity against planktonic and sessile cariogenic bacteria. These data are relevant and encourage further research into these plants, which may contribute to the discovery of new substances that can inhibit the growth of cariogenic microorganisms and reduce the incidence of dental caries.